The Influence of Motivation and Work Discipline on Employee Performance of PT PTI - Fauzobihi, Fauzobihi; Saputra, Ambara; Imanuddin, Kaffah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The motivation and employee discipline are a unit in the family of human resources science which certainly affects employee performance. This research uses quantitative research. The results of the study are, it can be seen that the results of testing the work motivation hypothesis have a significance level of 0.000 and a calculated t value of 5.351 > t table 1.66757. So it can be concluded that Ha is accepted, so it can be said that motivation (X) has a positive and significant effect on employee discipline because the level of significance of the motivation variable is < 0.05 (0.000 < 0.05) and the calculated t value is > t table ( 5.351 > 1.66757) In this research, employee work motivation suggests that discipline is one of the elements used in employee assessment which includes motivation to their work, position and organization. This discipline is reflected by the employee's willingness to protect and defend the organization inside and outside of work from being undermined by irresponsible people.